PENGEMBANGAN SISTEM ESTIMASI BIAYA PROYEK KONSTRUKSI BERBASIS KOMPUTER - I Nyoman Suardika; I Gusti Agung Adnyana Putera; Anak Agung Gde Agung Yana (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2019)
DEVELOPMENT OF COMPUTER BASED CONSTRUCTION PROJECT COST ESTIMATING SYSTEM ABSTRACT The process of calculating construction project cost estimates, especially detailed estimates, requires high accuracy and relatively long time depending on the size of the project, the number of estimators involved, the level of expertise and experience of the estimator. On the other hand, the advances in computer technology have not been fully optimized to aid cost estimation calculations. The objective of this research is to develop computer based cost estimation system of construction project. The system is designed to estimate project cost throughout the project life cycle both conceptual and detailed estimates. The method of development system used phased development which was modeled using Data Flow Diagrams (DFD) for process modeling, and Entity Relationship Diagram (ERD) for data modeling. Based on the results of weakness analysis on the old system, the proposed system architecture was using Client-Server Architecture model, with Microsoft SQL Server as database server. In the database server, it was created functions to serve requests for information sent by the client computer. To support the required information, the proposed concept integrated PBS (Product Breakdown Structure), WBS (Work Breakdown Structure) and RBS (Resource Breakdown Structure) to produce detailed cost estimation based on building components, work items and project resources. The cost estimation of the ongoing projects can be recorded as a database of cost estimation for future projects.